Early Peritoneal Dialysis and Postoperative Outcomes in Infants After Pediatric Cardiac Surgery: A Systematic Review and Meta-Analysis∗ - Namachivayam S.P. (2023)
Objective: Peritoneal dialysis (PD) is used in several cardiac surgical units after cardiac surgery, and early initiation of PD after surgery may have the potential to influence postoperative outcomes. This systematic review and meta-analysis aims to summarize the evidence for the association between early PD after cardiac surgery and postoperative outcomes. Data Sources: MEDLINE, Embase, and PubMed from 1981 to November 1, 2021. Study Selection: Observational studies and randomized trials reporting on early PD after pediatric cardiac surgery. Data Extraction: Random-effects meta-analysis was used to estimate the pooled odds ratios (ORs) and their 95% CIs for postoperative mortality and pooled mean difference (MD) (95% CI) for duration of mechanical ventilation and ICU length of stay. Data Synthesis: We identified nine studies from the systematic review, and five were considered suitable for meta-analysis. Early initiation of PD after cardiac surgery was associated with a reduction in postoperative mortality (OR, 0.43 (95% CI, 0.23-0.80); number of estimates = 4). Early commencement of PD shortened duration of mechanical ventilation (MD [95% CI], -1.09 d [-1.86 to -0.33 d]; I2= 56.1%; p = 0.06) and intensive care length of stay (MD [95% CI], -2.46 d [-3.57 to -1.35 d]; I2= 18.7%; p = 0.30], respectively. All three estimates had broad 95% prediction intervals (crossing null) denoting major heterogeneity between studies and wide range of possible study estimates in similar future studies. Overall, studies reporting on the effects of early PD included only a subset of infants undergoing cardiac surgery (typically high-risk infants), so selection bias may be a major issue in published studies. Conclusions: This review suggests that early initiation of PD may be associated with beneficial postoperative outcomes in infants after cardiac surgery. However, these results were based on studies of varying qualities and risk of bias. Early identification of high-risk infants after cardiac surgery is important so that prevention or early mitigation strategies can be applied to this cohort. Future prospective studies in high-risk populations are needed to study the role of early PD in influencing postoperative outcomes.